Detecting nestedness in city parks for urban biodiversity conservation - Rui-Qi Chen; Su-Ting Cheng (Urban Ecosystems, 2022)
Urbanization has been a global phenomenon producing great environmental and ecological challenges including species composition shifts in urban areas. To evaluate the interaction networks of the inhabitant metacommunities in urban parks, we applied the nestedness analysis using ecological survey data of birds, reptiles, frogs, and butterflies among 16 parks in Taipei City of Taiwan and identified critical environmental factors for biodiversity conservation. Results found significant nestedness of the metacommunities among these parks, which indicated strong interaction networks and the importance of urban parks for sustaining these metacommunities. In addition, various types of land use had different effects on the species incidence of birds, reptiles, frogs, and butterflies. It demonstrates that landscape design should consider the taxonomic differences in the development of conservation guidelines. Results also showed that the area of parks and the area of woodlot in the park were critical elements for the nested structure. Nonetheless, abundant bird generalists were found to be highly related to the area of buildings within parks, distance to forests, rivers, and the neighbouring parks. Moreover, exotic species were found to affect the interaction networks of native species. However, based on the current information, we cannot confirm the actual effects of the exotic species on the native assemblages. Reptiles and frogs appeared to be more easily threatened by land development and habitat fragmentation due to their lower vagility. In this regard, we suggest that conservation action should focus on preserving green space with large areas and constructing green corridors, creating crucial elements, and increasing the vertical complexity in the parks for species with various vagilities. We believe these strategies can help reduce the impact of urbanization to retain healthy interactions and connections of metacommunities among habitats for effective biodiversity conservation in urban areas.

Changes in the gut microbiota of osteoporosis patients based on 16S rRNA gene sequencing: a systematic review and meta-analysis - Rui Huang; Pan Liu; Yiguang Bai; Jieqiong Huang; Rui Pan; Huihua Li; Yeping Su; Quan Zhou; Ruixin Ma; Shaohui Zong; Gaofeng Zeng (Journal of Zhejiang University-SCIENCE B, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Insight into enhanced degradation of tetracycline over peroxymonosulfate activated via biochar-based nanocomposite: performance and mechanism - Tiehong Song; Yanjiao Gao; Jian Ye; Xin Zhang; Rui Su; Jiacheng Luo (Environmental Science and Pollution Research, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Neglected skin-associated microbial communities: a unique immune defense strategy of Bufo raddei under environmental heavy metal pollution - Rui Su; Sheng Zhang; Xueying Zhang; Shengnan Wang; Wenya Zhang (Environmental Science and Pollution Research, 2022)

Genome-wide identification of black pepper (Piper nigrum L.) Dof gene family and the differential gene screening in resistance to Phytophthora capsici - Fenju Zhang; Rui Fan; Lin Yan; Lisong Hu; Fan Su; Dewei Yang; Jing Li (Biologia, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Measurement Research on the Influence of China’s Provincial Technological Innovation Capacity upon Green Economy Development - Gang Ding; Xinyu Su; Rui Wang; Ladan Gui (Environmental Modeling & Assessment, 2022)

YOLO-Rip: A modified lightweight network for Rip currents detection - Daoheng Zhu; Rui Qi; Pengpeng Hu; Qianxin Su; Xue Qin; Zhiqiang Li (Frontiers in Marine Science, 2022)
Rip currents form on beaches worldwide and pose a potential safety hazard for beach visitors. Therefore, effectively identifying rip currents from beach scenes and providing real-time alerts to beach managers and beachgoers is crucial. In this study, the YOLO-Rip model was proposed to detect rip current targets based on current popular deep learning techniques. First, based on the characteristics of a large target size in rip current images, the neck region in the YOLOv5s model was streamlined. The 80 × 80 feature map branches suitable for detecting small targets were removed to reduce the number of parameters, decrease the complexity of the model, and improve the real-time detection performance. Subsequently, we proposed adding a joint dilated convolutional (JDC) module to the lateral connection of the feature pyramid network (FPN) to expand the perceptual field, improve feature information utilization, and reduce the number of parameters, while keeping the model compact. Finally, the SimAM module, which is a parametric-free attention mechanism, was added to optimize the target detection accuracy. Several mainstream neural network models have been used to train self-built rip current image datasets. The experimental results show that (i) the detection results from different models using the same dataset vary greatly and (ii) compared with YOLOv5s, YOLO-Rip increased the mAP value by approximately 4% (to 92.15%), frame rate by 2.18 frames per second, and the model size by only 0.46 MB. The modified model improved the detection accuracy while keeping the model streamlined, indicating its efficiency and accuracy in the detection of rip currents.

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

Evaluating the stability of Outang landslide in the Three Gorges Reservoir area considering the mechanical behavior with large deformation of the slip zone - Junbiao Yan; Zongxing Zou; Rui Mu; Xinli Hu; Jincheng Zhang; Wen Zhang; Aijun Su; Jinge Wang; Tao Luo (Natural Hazards, 2022)

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

Spirulina platensis aqueous extracts ameliorate colonic mucosal damage and modulate gut microbiota disorder in mice with ulcerative colitis by inhibiting inflammation and oxidative stress - Jian Wang; Liqian Su; Lun Zhang; Jiali Zeng; Qingru Chen; Rui Deng; Ziyan Wang; Weidong Kuang; Xiaobao Jin; Shuiqing Gui; Yinghua Xu; Xuemei Lu (Journal of Zhejiang University-SCIENCE B, 2022)

Transcriptomic Analysis of Circulating Neutrophils in Sheep with Mineral Element Imbalance - Di Wang; Ming Ji; Qijun Zhou; Chengyuan Su; Shuai Lian; Jianfa Wang; Jiasan Zheng; Rui Wu (Biological Trace Element Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Leaf and canopy photosynthesis of four desert plants: considering different photosynthetic organs - Zijuan Zhou; Peixi Su; Xiukun Wu; Haina Zhang; Rui Shi; Jianping Yang (Photosynthesis Research, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)